Community extension MSME's entrepreneurial activities in relation to poverty reduction - Valle, Lislee; Costan, Emily; Costan, Felix; General, Edralin; Alcantara, Gerly; Kilat, Ronnel Victor; Batican, Ivy; Olivar, Gladies Mae; Avila, Denilin (Frontiers in Sociology, 2022)
Higher Education Institutions play a role in poverty reduction by implementing community extension programs focusing on capacity building and entrepreneurship training. Cebu Technological University programs offer these programs through various skills training to its targeted beneficiaries. This study aims to assess the community extension Micro-, Small and Medium sized Enterprises (MSMEs) entrepreneurial activities concerning poverty reduction. The research participants are beneficiaries of community extension programs that primarily focus on capacity building and entrepreneurship training, and they eventually become entrepreneurs. Using a cross-sectional survey, 172 valid responses were analyzed, with entrepreneurship education (EE), budgeting financial literacy (BFL), access to credit facilities (ACF), and entrepreneurial performance (EP) as predictors of poverty reduction (PR). Results from Partial Least Squares - Structural Equation Modeling (PLS-SEM) generate insights from the 7 hypothesized paths of the proposed model. Findings revealed that entrepreneurship education, budgeting, financial literacy, and access to credit facilities help reduce poverty. However, no significant relationship was found between entrepreneurial performance and poverty reduction. This may be caused by a crisis (e.g. health crisis such as COVID-19) in which poverty and the pandemic significantly impacted the global and Philippine economies. MSMEs entrepreneurial activities are the primary victims of these crises. Even at a time of crisis, this confirms the importance of entrepreneurship education, budgeting, financial literacy, and credit access in promoting entrepreneurial success and reducing poverty.